Supporting women to take the lead in climate change adaptation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
CCAFS South Asia works with local partner organisations to empower women leaders and farmers to understand how best they can adapt to climate change and what resources they require to do so. We also map gender-related climate-smart agricultural practices, develop training materials on climate change adaptation and analyse adaptation policies from a gendered perspective.